Analysis of tasks and training load during pre-season training in professional basketball - Calle, P.; López-Sierra, P.; Feu, S.; Ibáñez, S. J. (Apunts Sports Medicine, 2025)
Introduction In the quest to improve basketball players' performance during the season, the analysis of the training processes during the pre-season is crucial to successfully face the competition period. The aim of this research was to characterize the training tasks of a professional basketball team of the ACB category during the 2022/23 pre-season, as well as to analyze the relationship between the game situation with the pedagogical variables and External Load variables.